Higher symptom burden is associated with lower function in women taking adjuvant endocrine therapy for breast cancer. Issue 2 (March 2019) - Sitlinger, Andrea; Shelby, Rebecca A.; Van Denburg, Alyssa N.; White, Heidi; Edmond, Sarah N.; Marcom, Paul K.; Bosworth, Hayden B.; Keefe, Francis J.; Kimmick, Gretchen G.
Abstract: Objective: To explore the impact of symptoms on physical function in women on adjuvant endocrine therapy for breast cancer. Methods: Eligible women were postmenopausal, had hormone receptor positive, stage I-IIIA breast cancer, completed surgery, chemotherapy, radiation, and on adjuvant endocrine therapy. At a routine follow-up visit, women (N = 107) completed standardized symptom measures: Brief Fatigue Inventory, Brief Pain Inventory, Menopause Specific Quality of Life Questionnaire, Functional Assessment of Cancer Therapy Neurotoxicity scales. Two performance measures assessed function: grip strength (Jamar dynamometer; n = 71) and timed get-up-and-go (TUG; n = 103). Analyses were performed with an overall symptom composite score. Correlations and multiple linear regression analyses were performed to test adverse effects on physical function. Results: The mean age was 64 years (range 45–84), 81% white, 84% on an aromatase inhibitor, and on endocrine therapy for mean 35 months (range 1–130 months). Dominant hand grip strength was inversely correlated with symptom composite scores (r = −0.29, p = .02). Slower TUG was positively correlated with higher Charlson comorbidity level (r = 0.36, p < .001) and higher symptom composite scores (r = 0.24, p = .01). In multivariate analyses, weaker dominant and non-dominant hand grip strength were significantly associated with greater symptom composite scores (β = −0.27, t = 2.43, p = .02 and β = −0.36, t = 3.15, p = .003, respectively) and slower TUG was associated with higher symptom composite scores (β = 0.18, t = 1.97, p = .05). Conclusions: Higher symptom burden is associated with worse physical function, as measured by hand grip strength and TUG. Further study to determine the impact of endocrine therapy and its side effects on function is warranted.